Application of Role Playing Method in Improving Students' Learning Motivation on Human Developmental Stages in Elementary School - Khasanah, Niswatun; Fardana, Yudistira; Inganah, Siti (Jurnal Pendidikan Edutama, 2025)
Students’ learning motivation is an important factor that influences the success of learning in elementary schools. The role-playing method has become one of the approaches that can enhance students' learning motivation on the topic of human development stages. Currently, learning in elementary schools often still uses conventional methods, which can decrease students' interest. By engaging in role playing, students are invited to actively participate and directly experience relevant roles, which is expected to enhance their involvement and understanding. This research aims to increase students' learning motivation through the application of role playing on human development stage material in elementary school. The research method used is classroom action research. Data collection was carried out by observing the implementation of learning using the role-playing method, observing students' learning motivation, and tests to measure learning outcomes. The results of classroom action research show an increase in the average of students' learning motivation between cycle I and cycle II, namely in cycle I the average of students' learning motivation was 63.5% to 85.4 in cycle 2. This increase in students' learning motivation is also related to the increase in students' learning outcomes between cycle I and cycle 2, namely in cycle 1 the average student score was 72.6 to 86.3 in cycle 2.